2000
DOI: 10.1006/gyno.2000.5729
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of a General Theory of Cervical Carcinogenesis Utilizing a Severe Combined Immunodeficiency Murine–Human Xenograft Model

Abstract: Objective. Currently, we lack a theoretical explanation for why squamous cell cervical cancer develops predominantly in specific sites (i.e., along the squamocolumnar junction). We therefore implanted human cervical tissues containing the transformation zone in severe combined immunodeficiency (SCID) mice and studied morphology, steroid effects, gene expression, and human papillomavirus (HPV) factors.Methods. Normal and dysplastic human cervical tissues (3 ؋ 2 mm) were placed subcutaneously in SCID-beige mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…In addition to possessing antiviral [6][7][8] and immunostimulatory [9][10][11][12] properties, catechins also exhibit antitumor [13][14][15][16] and antioxidative 11,17 effects. There is also sufficient evidence for antiangiogenic activity.…”
Section: Biologic Properties Of Green Tea Catechinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to possessing antiviral [6][7][8] and immunostimulatory [9][10][11][12] properties, catechins also exhibit antitumor [13][14][15][16] and antioxidative 11,17 effects. There is also sufficient evidence for antiangiogenic activity.…”
Section: Biologic Properties Of Green Tea Catechinsmentioning
confidence: 99%
“…Integration into the host genome, however, results in disruption of E2 and therefore loss of suppression of E6 and E7, resulting in disruption of p53 and pRB (retinoblastoma) signaling and oncogenesis. 6 The potential for integration and thus malignant transformation appears to vary among different HPV types, with HPV types 16 and 18 being most common in invasive lower genital tract cancers and HPV types 6 and 11 being associated Hastak et al 7 demonstrated that the EGCG-induced apoptosis in human prostate carcinoma cells is mediated through stabilization of p53 by phosphorylation on critical serine residues. Khafif et al 8 studied the effects of EGCG in an oral leukoplakia cell line and noted growth inhibition through a G 1 block that was induced with an increase in the underphosphorylated form of pRB.…”
Section: Antiviral Propertiesmentioning
confidence: 99%
“…For example, the mechanism by which the original squamocolumnar junction changes location after the onset of puberty may be due to swelling of the cervical stroma in response to hormonal stimulation and pregnancy is associated with more endocervical tissue moving out onto the ectocervix (Hendrickson and Kempson, 1997). The influence of estrogen exposure in the process of squamous metaplasia has also been shown in human TZ tissues implanted in SCID mice (Tewari et al, 2000).…”
Section: Role Of Sex Hormones In the Induction Of Squamous Metaplasiamentioning
confidence: 84%
“…Notch expression is associated with cell populations undergoing cell fate changes (e.g., columnar to squamous metaplasia at the transformation zone of the uterine cervix; ref. 35). The mammalian Notch genes (Notch-1 to -4) encode 300-kDa single pass transmembrane receptors.…”
Section: State Of the Sciencementioning
confidence: 99%